Comparison of bioactive components in fresh, pressurized, pasteurized and sterilized pennywort (Centella asiatica L.) juices - Arunee Apichartsrangkoon (2018)
The biologically active constituents of pennywort juice were analyzed by HPLC. The juice extract contained the bioactive glycosides, including asiaticoside and madecassoside. Antioxidant properties of juices were determined in terms of ferric-reducing antioxidant power assay, total polyphenol, β-carotene and ascorbic acid contents. After processing, asiaticoside, madecassoside and β-carotene in the extracted juice were relatively stable with no significant losses occurring. Pressurization could significantly retain ascorbic acid, polyphenols and antioxidant capacity than those pasteurization or sterilization. For storage assessment, asiaticoside in the processed juices was relatively stable during 4 months storage. Losses of ascorbic acid in the pressurized juice during storage were greater than in pasteurized and sterilized juice. However, the total amount of ascorbic acid retained in pressurized juice was still higher than those thermal-treated products. © 2012 Taylor & Francis.